(3eONd Edi EOGQI GdGYeGd GdOhdjI (B/s - (3CMeO , CMeO YHO GdQMefs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2001)
(3NdajGJ GbJUGOjI (B-(3EOGQI GdCYeGd GdOhdjI(B-(3fXQjI GdJLGQI GdNGQLjI(B-(3fXQjGJ GdGSJKeGQGdNGQLj(B-(3ejRGf GdeOahYGJ(B-(3GdGSJKeGQ GdCLfHj(B-(3HjFI EOGQI GdCYeGd GdOhdjI(B-(3JfXje hhXGFa GdCYeGd GdOhdjI(B-(3GdJNWjW GdGSJQGJjLj GdOhdj(B-(3GdJShjb GdOhdj(B-(3GdGOGQI GdeGdjI(B-(3GOGQI GdehGQO GdHTQjI(B- (3GdJUOjQ h GdGfJGL h GjLGO GdeUGOQ(B.s
(3eQGLY U(B.437s
Keywords: (3EOGQI GdCYeGds